Prevalence of malnutrition according to age groups in different communities of Costa Rica between 1997 and 2014 - Chinnock, Anne (2017)
Objective: to analyze the prevalence of problems in nutritional status of family members, according to age groups from different communities in Costa Rica between 1997 and 2014. Methods: an analysis of data collected by nutrition students of the University of Costa Rica between 1997 and 2014 is presented. All members of the selected families were weighed and their height measured. Growth references and cut-off points of World Health Organization were used in the analysis. Results: information for 25 studies collected during 17 years is presented. Among the under-20 age groups, with the passage of time, a reduction can be seen in prevalence of low weight and height and an increase in prevalence of excess weight or risk of excess weight. An increasing prevalence of excess weight can also be observed in the adults and amongst the elderly, there was a reduction in the prevalence of weight deficit.  Discussion: the information presented is compared to other publications which report similar results and the causes and consequences of excess weight are discussed. Conclusion: with the passage of time, a reduction was observed in the prevalence of low weight and height in the under-20 age groups and in the prevalence of low weight in the elderly.  There was an increase in the prevalence of excess weight in all the age groups.